Post-Monsoon Season Surveillance A Must for Curtailing Annual Dengue Epidemic in Rural India - Pradeep Aggarwal; Pratima Gupta; Sunil D Kandpal; Barnali Kakati; Divya Gupta (Medsci Publications, 2014)
Background: Dengue fever takes epidemic form annually. This incidence of epidemic proportions is usually related to the seasons of weather in the subcontinent especially monsoons. Objectives: The current study was planned to document whether there is a correlation of these weather conditions (over a period of five years period 2008-2012) with annual dengue epidemic's variability in the capital city of hill state of northern India that is largely rural areas covering tough mountainous terrains. Methods: The monthly meteorological data about monthly mean temperatures, monthly cumulative rainfall, and monthly mean relative humidity were collected from local office of India Meteorological Department for the years 2008-2012 in the capital city of hill state of northern India. Subsequently, the mandatory reports of the monthly incidence of new dengue cases for the same period were collected from District Headquarters for final correlation of dengue cases incidence with climate conditions. Results: The dengue epidemic peaked in Octobers after two-month lag period from the peaked rainfalls and relative humidity in Augusts. This rightward shift of dengue epidemic in relation to the weather graph of the city continued till the end of Novembers, even though monsoon seasons ended in Septembers. Conclusion: There is two-month lag period for incidence and peaking of dengue fever epidemic in comparison to the monsoon season suggesting the need of continuous dengue surveillance well beyond after the end of monsoon season.